PENGARUH SISTEM PENGENDALIAN INTERN, MORALITAS DAN KESESUAIAN KOMPENSASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Ni Luh Putu Asri Ayuni (UNHI Press, 2022)
Accounting fraud is a deliberate action with bad ethics that can harm the organization or company. This study aims to determine the effect of Internal Control, Morality, and Compensation Suitability on the Trend of Accounting Fraud in LPDs in Abiansemal District. The population in this study were employees at 31 LPD in Abiansemal District. The sample in this study was determined using the nonprobability sampling method with purpusive sampling technique or determining the sample with certain criteria, the sample in this study was LPD employees who had a large enough opportunity to commit fraud, so the number of samples in this study was 214 respondents. This research method uses quantitative research methods with primary data obtained from questionnaire data which is measured using a Likert scale research method. The data analysis technique used is descriptive analysis, validity test, reliability test, classical assumption test, multiple linear regression analysis, ANOVA or F test, coefficient of determination and t test. The results of this study are that internal control has a negative and significant effect on the tendency of accounting fraud, morality has a negative and insignificant effect on the tendency of accounting fraud, the suitability of compensation has a negative and significant effect on the tendency of accounting fraud.